KEEFEKTIFAN TEKNIK THINK PAIR SHARE DALAM PENINGKATAN PENGUASAAN KOSAKATA BAHASA JEPANG (Penelitian Eksperimen Terhadap Siswa Kelas XI IPS 1 SMA Muhammadiyah 1 Pekanbaru) - Rokhasiwi, Astari; Hadriana, Hadriana; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research discuss about the effectiveness of think pair share technique in increasing the mastery of Japanese vocabulary for XI IPS 1 students of SMA Muhammadiyah 1 Pekanbaru. The purpose of this study to determine whether the technique of think pair share effective to improve mastery of Japanese vocabulary class XI IPS 1 students of SMA Muhammadiyah 1 Pekanbaru. In this study, the writer used a weak experimental research design with marked by the absence of class comparison. The technique of collecting data by giving a test. The test results on pretest and posttest are increase, on pretest the students'average score is 66,5 whereas on posttest is 83. The test results are processed using statistical t-test manually to find out how much significant level of students learning outcomes when using the think pair share technique. Based on statistical test data processing found to = 7.78 and tt = 2.85 (5% significant level), to tt then H0 rejected and Ha accepted, it means that significant influence on the effectiveness of think pair share technique in increasing the mastery of Japanese vocabulary class XI IPS 1 of SMA Muhammadiyah 1 Pekanbaru.Keywords: Learning Vocabulary, Technique Think Pair Share, SMA Muhammadiyah 1 Pekanbaru